Pakiet edukacyjny „Gramy w piktogramy” – pomysł na wspieranie edukacji matematycznej dzieci i jego wykorzystanie w praktyce szkolnej - Mirosław Dąbrowski; Małgorzata Żytko (Problemy Wczesnej Edukacji)
The paper is based on research carried out by the Faculty of Education, University of Warsaw, between September 2012 and june 2013 in cooperation with Publishing House bohdan orłowski. During the research, innovative tool "We play pictograms" was tested. The tool was designed to support the development of mathematical skills of pupils at primary school level as well as to evoke the change to teachers’ attitude towards math teaching. The main research aim was increasing the level of maths comprehension and implementing the skills in practice by primary school pupils using Picto – innovative tool.